ФУНКЦОНАЛЬНАЯ РОЛЬ ФРАЗЕОЛОГИЧЕСКИХ ОБОРТОВ В ПРОЗЕ И.С. ТУРГЕНЕВА (Scientific journal of the Fergana State University, 2023)
The article considers the functional role of phraseological turns in the works of Turgenev and their wide use in  writer’sprose.